2023
DOI: 10.1371/journal.pntd.0011205
|View full text |Cite
|
Sign up to set email alerts
|

A drug repurposing screen for whipworms informed by comparative genomics

Avril Coghlan,
Frederick A. Partridge,
María Adelaida Duque-Correa
et al.

Abstract: Hundreds of millions of people worldwide are infected with the whipworm Trichuris trichiura. Novel treatments are urgently needed as current drugs, such as albendazole, have relatively low efficacy. We have investigated whether drugs approved for other human diseases could be repurposed as novel anti-whipworm drugs. In a previous comparative genomics analysis, we identified 409 drugs approved for human use that we predicted to target parasitic worm proteins. Here we tested these ex vivo by assessing motility o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Using an in silico screen, the authors also identified new promising drug targets from parasitic nematodes and platyhelminths and exploited a drug repurposing approach to prioritize potential anthelmintics. Recently, 409 of 817 proposed drugs were experimentally screened against the parasitic nematode Trichuris muris , and 50 of 409 drugs (~12%) showed complete or partial motility inhibition against adult worms ( 26 ). However, these efforts have not yielded candidates for broad-spectrum anthelmintics; sequence homology and orthology among disparate organisms can be complicated by exaptation and co-option (the repurposing of genes/proteins with similar sequences to serve different functions among dissimilar pathogens).…”
Section: Introductionmentioning
confidence: 99%
“…Using an in silico screen, the authors also identified new promising drug targets from parasitic nematodes and platyhelminths and exploited a drug repurposing approach to prioritize potential anthelmintics. Recently, 409 of 817 proposed drugs were experimentally screened against the parasitic nematode Trichuris muris , and 50 of 409 drugs (~12%) showed complete or partial motility inhibition against adult worms ( 26 ). However, these efforts have not yielded candidates for broad-spectrum anthelmintics; sequence homology and orthology among disparate organisms can be complicated by exaptation and co-option (the repurposing of genes/proteins with similar sequences to serve different functions among dissimilar pathogens).…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic screening using GIN parasites for anthelmintic has included screening against ex vivo adult parasites, egg hatch assay, larval stages, and infective third-stage larvae 32 . However, regarding GINs that infect humans, the throughput of these screens has been limited [32][33][34][35] . The free-living nematode Caenorhabditis elegans has been used as a surrogate model for GINs that infect humans 32,[36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%